2016
DOI: 10.1126/scitranslmed.aac4976
|View full text |Cite
|
Sign up to set email alerts
|

Smad7 gene delivery prevents muscle wasting associated with cancer cachexia in mice

Abstract: Patients with advanced cancer often succumb to complications arising from striated muscle wasting associated with cachexia. Excessive activation of the type IIB activin receptor (ActRIIB) is considered an important mechanism underlying this wasting, where circulating procachectic factors bind ActRIIB and ultimately lead to the phosphorylation of SMAD2/3. Therapeutics that antagonize the binding of ActRIIB ligands are in clinical development, but concerns exist about achieving efficacy without off-target effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 54 publications
(92 reference statements)
3
64
0
Order By: Relevance
“…Multiple factors, including inflammation cytokines, decreased food intake and neuroendocrine changes ( Oliff et al, 1987 ; Scott et al, 1996 ; Rivadeneira et al, 1999 ; Zhou et al, 2010 ; Sishi and Engelbrecht, 2011 ; Winbanks et al, 2016 ), contribute to the occurrence of cancer cachexia in vivo , which makes the mechanisms of cancer cachexia remain largely unknown. To make the question simple, here we used the in vitro system to investigate the mechanisms of PDTC on attenuating cancer cachexia.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple factors, including inflammation cytokines, decreased food intake and neuroendocrine changes ( Oliff et al, 1987 ; Scott et al, 1996 ; Rivadeneira et al, 1999 ; Zhou et al, 2010 ; Sishi and Engelbrecht, 2011 ; Winbanks et al, 2016 ), contribute to the occurrence of cancer cachexia in vivo , which makes the mechanisms of cancer cachexia remain largely unknown. To make the question simple, here we used the in vitro system to investigate the mechanisms of PDTC on attenuating cancer cachexia.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that increased circulating activins contribute to lean tissue loss in a number of cachexia models and that intracellular inhibition of Smad signaling, after gene delivery of the inhibitor Smad7, prevents muscle wasting associated with cachexia (42). In this study, we compared the therapeutic potential of the activin B and myostatin prodomains, alone and together, in the colon-26 (C26) model of cachexia (43).…”
Section: Discussionmentioning
confidence: 99%
“…Atrophy-associated genes and protein degradation. In many studies, the expression of various atrophy-associated genes, or "atrogenes," is used as a surrogate for protein degradation, especially the expression of those genes involved in the ubiquitin proteasome pathway (59). In this study, we examined the relationship between the expression of the four most commonly investigated atrophy-associated genes, i.e., MuRF1, MAFbx/atrogin-1, FOXO1, and FOXO3a, with proteasome activity.…”
Section: Discussionmentioning
confidence: 99%